Analysis of the Effect of Liquidity, Leverage, and Profitability on the Financial Performance of Companies in the Indonesian Capital Market - Basuki Toto Rahmanto; KMT Lasmiatun; Nursyam Ar; Ramli Toalib; Syamsinar Syamsinar (West Science Business and Management, 2024)
This study examines the influence of leverage, liquidity, and profitability on the financial performance of companies listed on the Indonesian Capital Market. A quantitative approach was utilized, involving 150 companies, with data measured using a Likert scale (1–5) and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that leverage and profitability significantly and positively impact financial performance, with profitability demonstrating the strongest effect. Liquidity also positively influences financial performance, albeit to a lesser extent. Collectively, the three variables explain 62% of the variance in financial performance, highlighting their interdependence and critical role in driving firm success. The study provides valuable insights for corporate managers and policymakers in emerging markets, emphasizing the importance of strategic financial planning to ensure sustainable growth.